2013
DOI: 10.1371/journal.pgen.1003635
|View full text |Cite
|
Sign up to set email alerts
|

Independent Evolution of Transcriptional Inactivation on Sex Chromosomes in Birds and Mammals

Abstract: X chromosome inactivation in eutherian mammals has been thought to be tightly controlled, as expected from a mechanism that compensates for the different dosage of X-borne genes in XX females and XY males. However, many X genes escape inactivation in humans, inactivation of the X in marsupials is partial, and the unrelated sex chromosomes of monotreme mammals have incomplete and gene-specific inactivation of X-linked genes. The bird ZW sex chromosome system represents a third independently evolved amniote sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 55 publications
0
37
0
2
Order By: Relevance
“…Although there is no chromosome-wide dosage compensation in chicken, Z-linked genes differ in their M:F expression ratios, with a tendency for dosage-sensitive genes to be more equally expressed between the sexes (Zimmer et al 2016), but the regulatory means through which this gene-specific dosage compensation is achieved are not fully understood (Discussion; Melamed and Arnold 2007;Mank and Ellegren 2009;Itoh et al 2010;Livernois et al 2013;Wang et al 2017). We reasoned that miR-2954-3p, with its strong male bias, broad expression, and preference for Z-linked genes might provide an alternative path to gene-specific dosage compensation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no chromosome-wide dosage compensation in chicken, Z-linked genes differ in their M:F expression ratios, with a tendency for dosage-sensitive genes to be more equally expressed between the sexes (Zimmer et al 2016), but the regulatory means through which this gene-specific dosage compensation is achieved are not fully understood (Discussion; Melamed and Arnold 2007;Mank and Ellegren 2009;Itoh et al 2010;Livernois et al 2013;Wang et al 2017). We reasoned that miR-2954-3p, with its strong male bias, broad expression, and preference for Z-linked genes might provide an alternative path to gene-specific dosage compensation.…”
Section: Resultsmentioning
confidence: 99%
“…That said, previous work has demonstrated that M:F expression ratios vary across Z-linked genes, such that the intrinsic male bias is counteracted for a subset of dosage-sensitive genes (Zimmer et al 2016), but it has not been clear how such gene-specific dosage compensation is achieved. A handful of Z-linked genes may be affected by local Z inactivation (Livernois et al 2013), although more extensive Z inactivation is not supported by patterns of allele-specific expression (Wang et al 2017). Additionally, it has been suggested that a small region of the chicken Z Chromosome might be enriched for dosage-compensated genes (Melamed and Arnold 2007), but the pattern was not recapitulated in another study (Mank and Ellegren 2009) and does not appear to be evolutionarily conserved (Itoh et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…However, both results achieved by Zimmer et al. (2016) and Livernois et al. (2013) were very limited in the number of loci they could assess, and neither we able to examine parent-of-origin effects.…”
Section: Discussionmentioning
confidence: 96%
“…One potent silencing mechanism is meiotic sex chromosome inactivation (MSCI), in which most of the genes are silenced on the sex chromosomes during meiosis in the heterogametic sex. MSCI occurs in mammals (Fernandez-Capetill et al 2003), but remains contentious in Drosophila (Hense et al 2007;Meiklejohn et al 2011) and birds (Schoenmakers et al 2009;Guioli et al 2012;Livernois et al 2013). One hypothesis put forward is that a key function of MSCI is to prevent SGEs from invading sex chromosomes, which may be particularly vulnerable in the heterogametic sex where they are unpaired.…”
Section: Sges and Sex Chromosome Turnovermentioning
confidence: 99%